Comparison of extubation response with Ambu AuraGain and endotracheal tube - Narayanaswamy, Harshith Thalagunda; Agarwal, Meenal; Agarwal, Surendra Kumar; Nagaraja, Rahul Sajjan (International Journal of Research in Medical Sciences, 2024)
Background: Airway management poses significant challenges for anesthesia and critical care providers. The Ambu Aura is an innovative supraglottic airway device that is compatible with magnetic resonance imaging. It is designed to be disposable, phthalate-free, and allows for the use of traditional cuffed tracheal tubes in patients of all ages. The present study was aimed to compare the hemodynamic changes and complications in endotracheal tube and Ambu AuraGain extubation in patients undergoing surgery. Methods: This was a randomized, controlled study conducted on 30 ASA I/II patients undergoing surgery. The patients were divided into two groups, group T (n 15): endotracheal tube and group A (n = 15): Ambu AuraGain respectively. The hemodynamic parameters such as heart rate (HR), mean arterial pressure (MAP) were measured at extubation and at 1 minute, 3 minutes, 5 minutes, 7 minutes, 10 minutes, 13 minutes and 15 minutes after extubation and compared between the groups. Results: Ambu AuraGain showed significant decrease in HR and MAP 1 minute, 3 minutes, 5 minutes, 7 minutes, 10 minutes, 13 minutes and 15 minutes after extubation when compared to endotracheal tube and it was found to be significant. Further, the frequency of cough (6.7% versus 26.7%; p=0.002) and laryngospasm (0% versus 13.3%; p=0.002) was lower in Ambu AuraGain when compared to endotracheal tube. Conclusions: Ambu AuraGain may be a viable alternative to traditional endotracheal tubes in clinical settings with good safety profile.